Macrophage beta2-adrenergic receptor is dispensable for the adipose tissue inflammation and function - Kasparas Petkevicius; Guillaume Bidault; Sam Virtue; Stephen A. Newland; Martin Dale; Aurelien Dugourd; Julio Saez-Rodriguez; Ziad Mallat; Antonio Vidal-Puig (Elsevier, 2021)
Objective: Neuroimmune interactions between the sympathetic nervous system (SNS) and macrophages are required for the homeostasis of multiple tissues, including the adipose tissue. It has been proposed that the SNS maintains adipose tissue macrophages (ATMs) in an anti-inflammatory state via direct norepinephrine (NE) signaling to macrophages. This study aimed to investigate the physiological importance of this paradigm by utilizing a mouse model in which the adrenergic signaling from the SNS to macrophages, but not to other adipose tissue cells, was disrupted. Methods: We generated a macrophage-specific B2AR knockout mouse (Adrb2ΔLyz2) by crossing Adrb2fl/fl and Lyz2Cre/+ mice. We have previously shown that macrophages isolated from Adrb2ΔLyz2 animals do not respond to NE stimulation in vitro. Herein we performed a metabolic phenotyping of Adrb2ΔLyz2 mice on either chow or high-fat diet (HFD). We also assessed the adipose tissue function of Adrb2ΔLyz2 animals during fasting and cold exposure. Finally, we transplanted Adrb2ΔLyz2 bone marrow to low-density lipoprotein receptor (LDLR) knockout mice and investigated the development of atherosclerosis during Western diet feeding. Results: We demonstrated that SNS-associated ATMs have a transcriptional profile indicative of activated beta-2 adrenergic receptor (B2AR), the main adrenergic receptor isoform in myeloid cells. However, Adrb2ΔLyz2 mice have unaltered energy balance on a chow or HFD. Furthermore, Adrb2ΔLyz2 mice show similar levels of adipose tissue inflammation and function during feeding, fasting, or cold exposure, and develop insulin resistance during HFD at the same rate as controls. Finally, macrophage-specific B2AR deletion does not affect the development of atherosclerosis on an LDL receptor-null genetic background. Conclusions: Overall, our data suggest that the SNS does not directly modulate the phenotype of adipose tissue macrophages in either lean mice or mouse models of cardiometabolic disease. Instead, sympathetic nerve activity exerts an indirect effect on adipose tissue macrophages through the modulation of adipocyte function.